Consumer grocery cart path tracking system using RFID - Jacama, Archel A. (2011)
Radio Frequency Identification (RFID) is a technology widely used nowadays as means of identifying objects. It is often used in inventory tracking and product managing systems. The ability of RFID tags to give out information when called makes work easier because it speeds up the process. Unlike other inventory methods, RFID is less time-consuming since the tag itself does the work for you. The project aims to track consumer paths by using passive HF RFID tags that are strategically placed in different parts of the shopping marker. A reader will be attached on the grocery cart. As the consumer moves the cart along the aisles of the shopping area, the reader will detect the tags that are placed all over the venue. When detection occurs, the RFID tag's information will be written on the CartPC's database and also will be sent to the server database in real time via wifi. Another feature of this project is the screen placed on the cart. When the reader detects a specified tag, a media file will be played. This element of the project can be a tool for the store owner to circulate information to the consumers and also a way to advertise as the consumers are shopping. The project is envisioned as a way for grocery owners to track their consumers' shopping routine for product placement and also as a way to inform the consumer details while the consumer is in their said shopping routine.